Risk of pancreatic cancer according to glycemic status in nonalcoholic fatty liver disease: a nationwide cohort study - Han Na Jung; Ji Hye Huh; Eun Roh; Bum Jun Kim; Minwoo Lee; Jwa-Kyung Kim; Joo-Hee Kim; Boram Han; Kyung-Do Han; Jun Goo Kang; Seong Jin Lee; Sung-Hee Ihm (Scientific Reports)
Abstract We investigated the association between glycemic status and pancreatic cancer risk in individuals with nonalcoholic fatty liver disease (NAFLD). This study included 1,093,832 individuals with NAFLD who underwent the Korean national health screening in 2009. NAFLD was defined as fatty liver index ≥ 30 after excluding heavy alcohol use and viral hepatitis. Multivariable Cox proportional hazards regression assessed the risk of pancreatic cancer according to glycemic status (normoglycemia, impaired fasting glucose [IFG], and diabetes mellitus [DM]). During a median follow-up of 10.3 years, 4124 (0.38%) developed pancreatic cancer. Compared to normoglycemic controls, the risk of pancreatic cancer was significantly higher in those with IFG (adjusted hazard ratio [aHR] 1.16; 95% confidence interval [CI] 1.08–1.25) and DM (aHR 1.48; 95% CI 1.37–1.60). The increased risk of pancreatic cancer with advanced hyperglycemia was consistent across subgroups, including obesity, smoking, and alcohol use. People without regular exercise showed a stronger association between hyperglycemia and pancreatic cancer compared to regular exercisers. In conclusion, hyperglycemia was associated with a higher risk of incident pancreatic cancer among people with NAFLD, independent of obesity and health behaviors. This suggests that hyperglycemia, even in IFG status, is an important modifiable risk factor for pancreatic cancer in NAFLD.